Complete genome sequence analysis of a predominant infectious bronchitis virus (IBV) strain in China - Liu, Xing-li (Virus Genes, 2008)
Infectious bronchitis (IB) is one of the major diseases in poultry flocks all over the world caused by infectious bronchitis virus (IBV). In the study, the complete genome sequence of strain A2 was sequenced and analyzed, which was a predominant IBV strain in China. The results indicated that there were mutations, insertions, and deletions distributed in the whole genome. The A2 virus had the highest identity to S14 and BJ in terms of full genome, whereas had a further distance to Massachusetts strains. Phylogenetic analysis showed that A2 isolate clustered together with most Chinese strains. The results of this study suggest that strain A2 may play an important role in IBV’s evolution and A2-like IBVs are predominant strains in China.